Characterization of wild yeasts isolated from artisan dairies in the Marche region, Italy, for selection of promising functional starters. (March 2021) - Agarbati, Alice; Marini, Enrica; Galli, Edoardo; Canonico, Laura; Ciani, Maurizio; Comitini, Francesca
Abstract: Ninety-two yeasts isolated from cheeses and different dairies in the Marche region (Italy) were identified and characterized as potential functional co-starter cultures. The prevalent isolates were Debaryomyces hansenii (58%), Candida zeylanoides (25%) and Yarrowia lipolytica (5.5%), while other species belonging to the Candida, Kluyveromyces, Moniliella and Yamadazyma genera were minorities. The yeasts identified were subjected to typing analysis with the purpose of clustering the biotypes to detect the strain specificity for each dairy. Furthermore, the occurrence of some functional and/or probiotic properties was evaluated. D. hansenii, C. zeylanoides and Y. lipolytica showed 16, 4 and 2 different biotypes, respectively. Y. lipol y tica biotype II and Candida parapsilosis biotype I exhibited high antioxidant activities. The unique Kluyveromyces lactis biotype showed a minimal ability to grow in the presence of bile salts at 37 °C and pH 2.5, but it exhibited high antioxidant activity. Most of the D. hansenii and C. zeylanoides biotypes showed relevant preliminary probiotic and technological traits. Thus, considering these preliminary evaluations, selected strains of C. zeylanoides, Y. lipol y tica and K. lactis could be proposed in association with lactic acid bacteria as innovative co-starters that are able to develop functional cheeses characterized by a distinctive aroma. Highlights: Ninety-two yeasts from cheeses and environments were studied. The prevalent isolates were Debaryomyces hansenii, Candida zeylanoides and Yarrowia lipolytica. Kluyveromyces, Moniliella and Yamadazyma genera were minorities. Yeasts identified underwent typing. Functional and/or probiotic yeast properties were evaluated.